Evaluación del efecto plaguicida de extractos etanólicos obtenidos del claviceps purpurea (2024)
The following project presents the ethanolic extraction of the compounds present in Claviceps Purpurea using a liquid-liquid and liquid-solid system, where the presence of alkaloids, flavonoids and anthocyanins was identified thanks to the obtaining of UV-VIS visible absorption spectra with absorbance peaks between 400 and 500 nm and physicochemical observation methods such as the Wagner and Dragendorff test. Once this was done, the evaluation of the pesticidal effect was carried out within an emulsified concentrate type formulation, obtaining a 100% insect mortality rate (Gryllidae) in less than 48 hours. This result suggests that, although the commercial pesticide (Numetrin) has a more effective active compound (Cypermethrin), the Claviceps Purpurea extract offers high sustained effectiveness and is shown to be a viable and sustainable alternative in the agricultural industry. Therefore, the parameters and conditions for the conceptual design of the production of the pesticide from the ethanolic extract obtained are determined, determining that 500 g of feed is required to obtain 213 ml of pesticide with an efficiency of 75%, suggesting process improvements for future explorations of combinations with other biological control methods for continued development in this field.